Conditional environmentalism of right-wing populism in power: ideology and/or opportunities? - Caiani, Manuela; Lubarda, Balša (Environmental politics, 2024)
This study focuses on right-wing populists (RWP) in power and their discourses and policy preferences on environmental issues. Through a content and frame analysis of electoral manifestos, party communication and semi-structured, in-depth interviews with party representatives, this paper examines whether ideological or contextual factors (political opportunities) determine RWP positioning on the environment. By focusing on the only three cases in Europe of RWP in government in a prominent position, i.e. alone or as a major coalition partner (also representing key ideological varieties of RWP), Law and Justice - PiS in Poland; Fidesz in Hungary and Lega in Italy, this study shows that ideological positions (and especially differences) are less important in determining RWP environmental discourses than are opportunities and institutionalization. Moreover, we also find that the shared features across these actors reflect a conditional, 'yes-but' environmentalism of these parties, embedded in the discourse of ecological modernization and oppositional, Manichean framing.